2013
DOI: 10.1128/jb.00080-13
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Reversals in Paenibacillus dendritiformis Swarming

Abstract: Bacterial swarming is a type of motility characterized by a rapid and collective migration of bacteria on surfaces. Most swarming species form densely packed dynamic clusters in the form of whirls and jets, in which hundreds of rod-shaped rigid cells move in circular and straight patterns, respectively. Recent studies have suggested that short-range steric interactions may dominate hydrodynamic interactions and that geometrical factors, such as a cell's aspect ratio, play an important role in bacterial swarmin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 64 publications
2
41
0
Order By: Relevance
“…including viscoelasticity [57]). Further developments should also include the active motility and the chemomechanical interactions occurring at the microscopic scale inside the colony, which are of fundamental importance in the appearance and evolution of patterns in some bacterial strains [10,25,26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…including viscoelasticity [57]). Further developments should also include the active motility and the chemomechanical interactions occurring at the microscopic scale inside the colony, which are of fundamental importance in the appearance and evolution of patterns in some bacterial strains [10,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…However, we remark for sake of completeness that some bacteria also possess other motility mechanisms for colonization. For example, recent studies on Paenibacillus dendritiformis [25] and on myxobacteria [26] have shown that very long bacterial cells do not swarm with the standard dynamic patterns of whirls and jets, but they rather form long tracks in which each individual bacterium periodically reverses its direction, moving back and forth along moderately curved lines. The short time between this direction switching was found to be independent of the number of neighbours and the environmental factors, suggesting the existence of an extraordinary robust internal clock for reversal events in bacteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…P. aeruginosa TFP or flagella confer multiple motility modes in addition to swarming, including swimming, twitching, crawling, and walking (15)(16)(17); P. aeruginosa requires a functional flagellum to swarm (18,19). Although the fastest swarming bacteria (i.e., species of Vibrio or Proteus) transition to a hyperflagellated state or can evolve as hyperflagellated mutants (20)(21)(22)(23), for this study, we have investigated monoflagellated bacteria characteristic of P. aeruginosa swarming. Both TFP and flagella are important to P. aeruginosa biofilm formation (24) and mediate attachment to different surfaces, including eukaryotic epithelial cells (25).…”
Section: Significancementioning
confidence: 99%
“…For example, Paenibacillus dendritiformis posess internal clocks that allow changes in direction independent of environmental cues [4]. Viswanathan et al characterized the movement of Diomedea exulans [21], and Humphries et al described Thalassarche melanophrys [13] searching for pelagic prey as statistically driven, where the pattern of motion is fractal, that is the distribution of step lengths is similar at all scales, defined as a Lévy flight.…”
Section: Adaptive and Stochastic Search Strategiesmentioning
confidence: 99%